Socializing Fragrant River Program as a Strategy for Introducing Environmental Literacy to the Upper Citarum Community - ANWAR, Rully Khairul; SJORAIDA, Diah Fatma; RAHMAN, M. Taufiq (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
This study aims at finding out how the processes of socialization to make a river became fragrant in Bandung, West Java, Indonesia. By this socialization, there was a hope for introducing environmental literacy to the community, so that appeared the idea of the Fragrant River of Citarum. Having socialized, there were series of knowledge, cognitive skills, attitudes and responsibilities examined to introduce environmental literacy to the community, especially the upper Citarum inhabitants. This study is qualitative in method and a case study in approach. Through such data collection techniques as observation, interviews, and documentation studies this writing follows the Miles and Huberman’s interactive model in analyzing the data. The results of this study show that the environmental information literacy owned by the residents of the upper Citarum River is not good in maximizing the information and knowledge they have for the surrounding environment. However, Citarum Fragrant program was very effective in bring the information and knowledge to the community in overcoming the waste dumped to the river.